OP4 Ubiquitin proteosome pathway; a novel therapeutic target in vascular calcification. (5th April 2020) - Phadwal, Kanchan; Kurian, Dominic; Thomas, Benjamin; Cawthorn, Will; MacRae, Vicky E
Abstract : Vascular calcification (VC), a pathophysiological consequence of atherosclerosis and arteriosclerosis, is associated with an inevitably stiffened arterial system, leading to development of cardiovascular diseases. Currently, there are no effective strategies for treating vascular calcification. Caloric restriction (CR) is a dietary intervention that involves reduction of total calories below ad libitum intake without nutritional insufficiency or malnutrition. Over the past decade the potential for CR to delay the onset of age-related chronic diseases and offer direct cardioprotective effects have become well recognised. However, the effect of CR on VC has yet to be examined. We isolated VSMCs form the aortae of CR mice and cultured them under calcifying conditions (3mM Pi) ex vivo . VSMCs derived from CR mice showed reduced calcification compared to VSMCs from mice fed ad libitum (p<0.0001). To test this in vitro we starved rat valve interstitital cells for 48hrs (RVICs) and primary vascular smooth muscle cells (VSMCs) for 96hrs by culturing them in HBSS along with treating them with high dosage of calcium (Ca) and phosphate (Pi) (2.7mM Ca/2.5mM Pi for RVICs and 3mM Pi for VSMCs). The starved RVICs and VSMCs show reduced calcification compared to the cells grown in normal calcifying media enriched with serum and glucose (p<0.0001). These starved cells show reduced expression of key calcifying marker Runx2 (3 fold decrease, p<0.0005) and PHOSPHO1 and a concomitant increase in the calcification inhibitor ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1, 3 fold increase, p<0.0006). To investigate the molecular mechanism underpinning starvation-induced abrogation of VC, we carried out stable isotope labeling by/with amino acids in cell culture (SILAC) based quantitative proteomics comparison between calcified and starved RVICS. The majority of proteins showing >2 fold upregulation were from the ubiquitin proteasome system (UPS). UPS is a selective proteolytic system in which substrates are recognised and tagged with ubiquitin for processive degradation by the proteasome. Treatment of both RVICs and VSMCs with MG132 (UPS inhibitor; 10uM) cultured under calcifying conditions accelerated calcification in both cell types(p<0.0001). Together these data suggest that CR protects against VC by degrading crucuial regulators of calcification including PHOSPHO1 and Runx2. This novel finding could lead to the application of CR-mimetics to combat vascular calcification.